জীবনের বালুকাবেলায় - চৌধুরী, ফারুক (ঢাকা : প্রথমা প্রকাশন, 2014)
Autobiography of Phāruka Caudhurī, former diplomat from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Caudhurī, Phāruka; Diplomats -- Bangladesh -- Biography; Bangladesh -- Foreign relations